2021
DOI: 10.17263/jlls.904145
|View full text |Cite
|
Sign up to set email alerts
|

The perception of blackboard collaborate-based instruction by EFL majors/teachers amid COVID-19: A case study of Saudi universities

Abstract: This paper investigates the perception of using Blackboard Collaborate-based Instruction (BCI) by Saudi EFL majors and teachers during the crisis of COVID-19 pandemic. The paper's main objective is to explore the extent to which modern technologies contribute to the process of teaching and learning English at Saudi universities. This is conducted by probing the benefits and challenges of using Blackboard Collaborate as a digital platform through which the different university courses are taught. The study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 20 publications
12
59
0
1
Order By: Relevance
“…The result of this study reveals that students' perceptions are positive as the results show that students are aware of the benefit of the Blackboard platform during the COVID-19 pandemic. This result goes in line with Almelhi (2021), Chen et al (2020), andKhafaga (2021), who reported that students have positive attitudes towards the Blackboard platform. However, Almekhlafy (2020) reported that the students' perceptions towards Blackboard were not positive .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The result of this study reveals that students' perceptions are positive as the results show that students are aware of the benefit of the Blackboard platform during the COVID-19 pandemic. This result goes in line with Almelhi (2021), Chen et al (2020), andKhafaga (2021), who reported that students have positive attitudes towards the Blackboard platform. However, Almekhlafy (2020) reported that the students' perceptions towards Blackboard were not positive .…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the majority of the students perceived that Blackboard gives the feeling that they are responsible for the learning process. This seems to chime with Hamad's (2017) and Khafaga's (2021) contention that Blackboard fosters independent learning. A further result is the students' perception that the Blackboard is a good and positive educational tool, as it gives pleasure in learning and helps to enhance the quality of learning.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…English language related studies during the Covid-19 process (between March 2020 and February 2021) (Aji et al, 2020;Allo, 2020;Almekhlafy, 2020;Andriivna et al, 2020;Ariyanti, 2020;Astuti & Solikhah, 2021;Atmojo & Nugroho, 2020;Bailey & Lee, 2020;Chiatoh & Chia, 2020;Dahmash, 2020;Davies et al, 2020;Destianingsih & Satria, 2020;Farrah & Al-Bakry, 2020;Fatima, 2020;Fitria, 2020;Forrester, 2020;Fuad et al, 2020;Fuentes Hernández et al, 2020;Gao & Zhang, 2020;Hadianti & Arisandi, 2020;Hafidz, 2020;Hakim, 2020;Hamid, 2020;Hartshorn & Mcmurry, 2020;Hazaea et al, 2021;Hodges et al, 2020b;Hopp & Thoma, 2020;Huang et al, 2021;Kamhi-Stein et al, 2020;Karakuzu et al, 2020;Karataş & Tuncer, 2020;Karim & Hasan, 2020;Kawinkoonlasate, 2020;Khafaga, 2021;Kholis, 2020;Krishan et al, 2020;Kusumawati, 2020;Li et al, 2020;Lie et al, 2020;Loo, 2020;…”
Section: Study Focus Authors Nmentioning
confidence: 99%